Analisis Biaya dan Kualitas Hidup Pasien Kanker Paru Non-Small Cell Lung Cancer (NSCLC) Mutasi Epidermal Growth Factor Receptor (EGFR) - Eliyanti, Uzma; Tyas, Rafi Setyoning; Hapsari, Indri; Setiawan, Didik (Universitas Islam Indonesia, 2025)
Introduction: Lung cancer remains a leading cause of death worldwide, with non-small cell lung cancer (NSCLC) carrying the highest incidence among lung cancer types, particularly in patients with epidermal growth factor receptor (EGFR) mutations. The first-line therapy for NSCLC lung cancer patients with EGFR mutations typically involves the tyrosine kinase inhibitor (TKI) group.Objective: The study aimed to compare the cost utility of the two TKI groups (afatinib and erlotinib) for NSCLC patients with EGFR mutations.Methods: This pharmacoeconomic study was conducted using the Cost Utility Analysis (CUA) method from the patient’s perspective. The study included 33 patients receiving afatinib and 12 patients receiving erlotinib, conducted in 2022-2023 at Kariadi Hospital, Semarang, and Prof. Dr. Margono Soekarjo Hospital, Purwokerto. Therapeutic outcomes were measured using Quality Adjusted Life Year (QALY), and cost components included actual costs and estimated costs based on clinical pathways. CUA was presented in the form of an Incremental Cost Effectiveness Ratio (ICER).Results: The cost of afatinib was greater than that of erlotinib (IDR 174.395.847 vs. IDR 138.672.688). The quality of life of afatinib was better than that of erlotinib (0.397 vs. 0.161, p-value 0.016). The ICER of afatinib was IDR 151.369.318 per QALY when compared to erlotinib.Conclusion: This study demonstrates that afatinib is a cost-effective treatment option for NSCLC patients with EGFR mutations.